2013
DOI: 10.1017/s0014479713000306
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Maize-Based Cropping Systems for Smallholder Malawi Farmers Using Conservation Agriculture Technologies

Abstract: SUMMARYAgricultural production in southern Africa is constrained by numerous factors, including low soil fertility, frequent droughts and flooding, limited access to fertilizers and the use of unsustainable management techniques that increase soil erosion rates. Conservation agriculture (CA) is based on the principles of minimum soil disturbance, crop residue retention and crop rotations. CA systems have been proposed to alleviate the negative externalities associated with conventional crop management systems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 35 publications
2
38
1
Order By: Relevance
“…Thus, it is necessary to consider site-specific conditions in determining the financial attractiveness of CA. Even where the financial incentives may appear attractive, a consideration of non-financial factors (e.g., risk of crop failure) is required to understand the actual and potential adoption of CA 112 . …”
Section: Effects Of Ca On Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is necessary to consider site-specific conditions in determining the financial attractiveness of CA. Even where the financial incentives may appear attractive, a consideration of non-financial factors (e.g., risk of crop failure) is required to understand the actual and potential adoption of CA 112 . …”
Section: Effects Of Ca On Productivitymentioning
confidence: 99%
“…However, these past researches were largely conducted within experimental stations and did not take into account socio-economic constraints in real farm situations that could hinder the widespread adoption of CA. Recently, more studies reporting results from onfarm and on-station trials have been published concentrating on some of the above-mentioned challenges and constraints 28,37,68,73,86,94,96,97,99,101,102,104,[113][114][115][116] .…”
Section: Constraints To Adoption Of Ca Systems In Southern Africamentioning
confidence: 99%
“…Ngwira, Thierfelder, Eash, and Lambert (2013) found that profits for maize produced under CA systems were 61% to 116% higher than profits produced by conventional tillage practices ($344 ha -1 ). Mazvimavi and Twomlow (2009) and Guto, Pypers, Vanlauwe, de Ridder and Giller (2011) found that profit margins for crops produced with minimum tillage technologies were superior to net returns produced under conventional systems.…”
Section: Introductionmentioning
confidence: 95%
“…Mazvimavi and Twomlow (2009) and Guto, Pypers, Vanlauwe, de Ridder and Giller (2011) found that profit margins for crops produced with minimum tillage technologies were superior to net returns produced under conventional systems. Ngwira et al (2013) found that risk-averse farmers preferred CA systems compared to conventional tillage systems, with risk premiums for conservation agriculture systems (relative to conventional farming methods) ranging between $40 and $105 US dollars. Most of these studies compared the profitability of CA systems with conventional farming practices using partial budget analysis (e.g., Boehlje & Eidman, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing CA maize systems with conventional tillage systems, studies conducted across the country reported that the former has less labour costs, has higher gross margins and lowers risk of crop failure (Ngwira et al, 2011;Ngwira et al 2012a;Ngwira et al, 2013;Wall et al, 2013;Ngwira et al, 2014a;Thierfelder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%